OP48 Age, sex and socioeconomic inequalities in fruit and vegetable intake in uk adults, 1986–2012. (2nd September 2017) - Yau, A; Adams, J; Monsivais, P
Abstract : Background: Low fruit and vegetable (FV) consumption is associated with cardiovascular disease and some cancers. The UK recommendation is that adults should consume at least 400 g (5 × 80 g portions) of FV per day. However, the most recent available data indicate that over 80% of UK adults do not adhere to the '5-a-day' recommendation. This study investigates whether the level of adherence has changed over time. Further, we look at number of FV portions consumed by age, sex and socioeconomic position across the three time points between 1986 and 2012. Methods: We used three surveys for this repeated cross-sectional analysis: the National Diet and Nutrition Survey (2000/01 and 2008/12) and a similar survey from 1986/87, the Dietary and Nutritional Survey for British Adults. These surveys employ multistage random sampling. FV intake was assessed using food diaries and demographic information collected by an interviewer. We included adults aged 19 to 64, who adequately completed a food diary, which gave sample sizes of 2047, 1724 and 1512, in 1986/87, 2000/01 and 2008/12 respectively. To test for socioeconomic inequalities, respondents were categorised into four groups (professional/managerial (I/II); skilled non-manual (IIINM), skilled manual (IIIM); partly skilled/unskilled (IV/V)) based on the Registrar General Social Class classification and we looked at absolute and relative differences between I/II and IV/V. To test differences in mean intake by demographic characteristics, we used t-tests and linear regression. All analyses were conducted in StataSE 13. Results: Overall FV intake increased by 20% from 1986/87 (2.67 portions, 95% confidence interval [2.59, 2.74]) to 2008/12 (3.21 portions [3.10, 3.32]), but still fell short of the recommended 5 portions. We found higher FV intake in socioeconomic group I/II compared to IV/V across all years (difference of 0.96–1.28 portions; 26.09%–36.36%). FV intake also differed by age across all surveys, with older respondents eating more than younger respondents (1.03–2.08 portions; 51.76%–129.19%). Men ate significantly more FV than women in 1986/87 (0.18 portions; 6.52%) but there was no significant difference in the latter time points. Conclusion: While FV consumption has increased in the UK since 1986, and sex differences in consumption have disappeared, socioeconomic and age-related inequalities persist. Population-level strategies to improve diet and increase FV intake are still needed in the promotion of public health. In order to redress inequalities, it is crucial that these strategies are at least or more effective in lower versus higher socioeconomic groups, and in younger versus older adults.